Novel 4-benzoylpyridine oxime derivative GIZH-298 with aticonvulsant activity - L. A. Zhmurenko; G. V. Mokrov; L. N. Nerobkova; S. A. Litvinova; I. O. Gaydukov; T. A. Voronina; T. A. Gudasheva (Фармакокинетика и Фармакодинамика)
Novel derivative of benzoylpyridine oximes - GIZH-298 (4-benzoylpyridine 0-(2-morpholinoethyl) oxime oxalate) was designed and synthesized in this work. This compound has a broad spectrum of anticonvulsant effects, eliminating primary generalized seizures in maximal electroshock (MES) and corazol antagonism tests in rodents in the doses of 0,5-100 mg/kg. LD50 for compound GIZH-298 is 316 mg/kg intraperitoneally (mouse). GIZH-298 has a large therapeutic breadth.